Radio-frequency plasma reduction of silver ions impregnated into a natural zeolite framework - Osonio, Airah P.; Vasquez, Magdaleno R. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The process of 13.56 MHz radio-frequency (RF) plasma treatment was successful in the reduction of silver ion (Ag+) to its metallic state while keeping the zeolite template stable. Plasma reduction has been reported as a green, dry, and energy-efficient alternative method of synthesis of Ag nanoparticles (NPs) loaded into porous templates, such as zeolite, via wetness impregnation. The study explored the effect of gaseous discharges [argon (Ar), oxygen (O2), and 1:1 Ar:O2] and exposure time (30 min, 60 min, and 90 min) to the fabricated composites, and their potential application as an antibacterial agent. 12.73% loading of Ag+ was determined by Atomic Absorption Spectroscopy for the chosen precursor solution of 0.20 M AgNO3 used all throughout the study. Characterization of the untreated and plasma-treated silver-zeolite (AgZ) composites were done using x-ray photoelectron Spectroscopy (XPS), x-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FTIR), field emission scanning electron microscopy with energy dispersive x-ray spectroscopy (FESEM-EDX), and Brunauer, Emmett and Teller (BET) surface analysis. XPS and XRD showed that the supported metal ions were completely reduced to metallic species, independent of the composition of the gas discharge used, without affecting the crystallinity of the zeolitic framework. Ag NPs of crystallite size ranging from 10.71 nm to 39.92 nm were approximated using the slow scan XRD spectra of the composites. SEM morphological analyses confirmed the presence of agglomerated Ag NP clusters on the surface, while BET results suggested the presence of the NPs within the channels of the microporous network with the increase in the average pore width from 11.97 A to 17.35 A upon plasma treatment. Moreover, SEM micrographs illustrated the sputtering effect of the gaseous discharges with increasing exposure time; the effect was found to be more pronounced using 02 plasma, than Ar and Ar:O2 discharges. EDX results suggested that plasma treatment led to partial dealumination, with the increase in the Si / Al ratio at extended exposure times, and the indiscriminate sputtering of surface elements with the decrease in Ag concentration after 90 min exposure. The antibacterial activity of the samples were tested against a gram positive (Staphylococcus aureus) and a gram negative bacteria (Escherichia coli) using the disk diffusion method. All plasma-treated AgZ samples exhibited considerable antibacterial index against the two bacteria, from 0.16 to 0.62, but the highest value was determined with the sample treated for 60 min using O2 plasma. The result is hypothesized to be an effect of the increased contact between the composite and bacterial culture with roughened surface induced by plasma treatment and the possible inclusion of reactive oxygen species that may have contributed to the overall antibacterial activity of the composite. Overall, the fabrication of AgZ composites via RF plasma reduction is ideal for different surface-based processes in the biomedical field due to its induced antimicrobial sensitivity. This plasma-induced reduction technique may also find applications in adsorption and catalysis.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Zeolites; Silver; Ion exchange; Reduction (Chemistry)